Dictionary of American conservatism - Filler, Louis,Kirk, Russell (Philosophical Library, 1987)
Louis Filler: Dictionary of American Conservatism. The First Complete Guide to Issues, People, Events, Organizations, Philosophical Library Inc., New York 1987. 380 Seiten, 29,95 Dollar
Keywords: Wörterbuch; Conservatism